The arena of racism - Wieviorka, Michel, 1946- (London ; Thousand Oaks, Calif. : Sage Publications, 1995)
This translation of Michel Wieviorka's L'espace du racisme is the most important addition to the sociological literature on racism published thus far. Although The Arena of Racism presents a detailed and revisionary analysis of the "vocabulary" of racism (prejudice, discrimination, segregation, and violence), Wieviorka argues that racism is not reducible to these "elementary forms." He uses the experiences of institutionalized racism in America and antisemitism in Europe to situate an analysis of the complex transition from race to racism. Wieviorka has written an essential analytical rather than simply historical study of racism. He argues that racism has to be understood as an action related to factors fixed in the dislocation between the social and the communal. As the social relations defined by industrial capitalism are in decline, so too are ideas of progress and universality. It is in this context, of postmodern social and economic flux, that Wieviorka sculpts a definition of racism. Wieviorka has referred to his work as "an integrated set of analytical instruments." Faculty and scholars in the areas of sociology, cultural studies, race relations, and political science will find The Arena of Racism to be one of the key texts to be published on the sociology of racism in the last 10 years.
Pt. I. From race to racism. Introduction -- 1. Race as Explanatory Principle -- 2. Race Relations -- 3. Prejudice and Personality -- 4. Racism as Ideology -- Conclusion -- Pt. II. The elementary forms of racism. Introduction -- 5. Levels and Logics of Racism -- 6. Prejudice -- 7. Segregation, Discrimination -- 8. Racist Violence -- Conclusion -- Pt. III. The unity of racism. Introduction -- 9. Social Movements and Racism -- 10. Two Patterns of Racism -- 11. Communal Identity and Racism -- Conclusion: The Unity of Racism.
Includes bibliographical references (p. [128]-144) and index.
The Roger Griffin ComFas Collection
Keywords: Racism; Racism -- France